The Influence of Customary Law in Settlement of Social Problems in the Middle of the Globalization Era - Damayanti, Sri; Ihsan Kurnia, Fajar; Labibah, Salma; Yulmaniar Putri, Hanifah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The era of globalization brings great challenges to indigenous peoples, especially in their efforts to maintain traditional values ​​amidst rapid social, economic and cultural changes. This article discusses the influence of customary law in resolving social problems in the era of globalization, including its role, challenges and relevance amidst modern dynamics. Customary law, which is rooted in local wisdom, has a crucial role in handling agrarian conflicts, preserving the environment, and strengthening the cultural identity of indigenous peoples. Nevertheless, customary law faces various challenges, such as modernization pressures, global cultural influences, and a lack of formal recognition by the state. These challenges often threaten the sustainability of customary law, especially in societies increasingly affected by cultural homogenization and shifting values. In this context, this article highlights the importance of formal recognition of customary law by the government and the need for education based on local wisdom to preserve traditional values. Through a collaborative approach between the government, indigenous communities and other parties, customary law can continue to be a relevant instrument in resolving social problems and maintaining cultural harmony amidst the challenges of globalization. Thus, customary law not only functions as a conflict resolution mechanism but also as a support for cultural identity and diversity in Indonesia. Keywords: Customary Law, Social Issues, Globalization